AVALIAÇÃO ELETROMIOGRÁFICA DOS MÚSCULOS DO ASSOALHO PÉLVICO DE MULHERES PRATICANTES DE CROSS TRAINING: UM ESTUDO TRANSVERSAL - Sidineia Silva Pinheiro Cavalcante Franco (2024)
Introduction: Stress Urinary Incontinence (SUI) is defined as the complaint of any involuntary loss of urine during effort, exercise, coughing or sneezing. One of the most practiced modalities by women today is cross training, which makes it important to evaluate the occurrence of UI in these women. Objective: To compare the bioelectrical activity of the pelvic floor of healthy sedentary women with that of women practicing cross training with and without UI. Methods: Cross-sectional study, composed of sedentary women and women who practice cross training, the International Consultation on Incontinence Questionnaire – Short Form ICIQ-SF was used to categorize the sample into three groups: sedentary group without UI - CG (n=16) , group of cross-trainers without SUI - G1 (n=14) and group of cross-trainers with SUI – G2 (n=15). The assessments also involved sociodemographic questionnaires, Questionnaire for Urinary Incontinence Diagnosis- QUID-Br- Version in Portuguese, Three Incontinence Questionnaire- 3IQBbr, and surface Electromyography to evaluate the bioelectrical activity of the PFM muscles using the Glazer Protocol. The data obtained were analyzed using the Kruskal-Wallis test, followed by Dunn's post-test, chi-square test, with Bonferroni correction, when necessary. The other results of this study were presented in the form of descriptive statistics or in the form of tables and graphs. Results: 45 women were evaluated, with average ages for the three groups of 35.19±1.74; 37.20±1.48 and 32.12±1.73 respectively. It was observed that the percentage of women who reported “I lose it when I am doing physical activities” was 66.7%. The QUID-Br and 3IQ-Br questionnaire showed that the most predominant type of UI was SUI with 93.3% of women complaining of UI. Regarding the EMG results, we obtained a significant difference in the items time(s) of pelvic floor muscle endurance, where this time was shorter among women practicing cross training with SUI in relation to the group of sedentary women. Another finding with a significant difference was in the mean peaks of fast and slow contractions of the MTA, which was higher among women who exercise and without SUI when compared to sedentary women. Conclusion: This study verified a correlation between the occurrence of SUI and a low bioelectrical activity of the transversus abdominis and an endurance deficit in the pelvic floor muscles.